Peran Tegak Nem Dase Nem Dalam Pujawali Agung di Pura Puseh Desa Busungbiu Kabupaten Buleleng - Ketut Trinadi; Ni Luh Gede Hadriani; Nyoman Suka Ardiyasa (Kamaya: Jurnal Ilmu Agama, 2026)
Tegak Nem Dase Nem is a hereditary genealogical and ritual institution that plays a central role in preserving religious traditions and customary life in Busungbiu Traditional Village, Buleleng Regency, Bali. As an institution inherited through the purusa lineage system, it possesses historical legitimacy as the descendants of the village founders and serves as an important element in the implementation of Pujawali Agung at Pura Puseh. This study aims to analyze the role, existence, and impact of Tegak Nem Dase Nem in the implementation of Pujawali Agung. This research employed a qualitative method with a descriptive-interpretative approach. Data were collected through participant observation, in-depth interviews, documentation, and literature studies involving customary leaders, temple priests, members of Tegak Nem Dase Nem, and community members. Data were analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that Tegak Nem Dase Nem, together with the Pemubug, forms a ritual structure of 99 members responsible for maintaining the orderly and sacred implementation of Pujawali Agung. Religiously, it safeguards ritual sanctity and spiritual discipline. Socially, it strengthens solidarity, cooperation, and community integration. Symbolically, it reflects cosmological harmony based on Tri Hita Karana. It also functions as a medium for transmitting customary knowledge, ritual ethics, cultural values, and character education to younger generations. In conclusion, Tegak Nem Dase Nem remains vital for preserving ritual traditions, strengthening social cohesion, and sustaining the cultural identity of the Busungbiu Traditional Village community.